Propuesta de reforma al numeral 33 artículo 42 del código del trabajo tendiente a incrementar el número de personas con discapacidad a ser incluidas como empleados del sector público y privado - Paladines Espinosa, Esther Bolivia (2017)
Since the origins of man in the primitive community the implementation of activities for the survival of the human being individually and collectively was necessary; including hunting, fishing, cultivation of various grains and vegetables, among others; this would represent the first form of work known throughout history. With the social and productive evolutionary process, work was established in a man's responsibility and a right recognized by the laws, since its implementation not only through are products get to meet different market needs, but also achieves financial or in kind, by which it can subsist who performs work or task. These guidelines make up our labor legislation, becoming a right and a social duty fully recognized and protected by the state, which assumes a fundamental transformation in relation to society. In recent years there have been several reforms throughout the legal framework, giving priority to vulnerable groups, such as: Children and adolescents, the elderly, people with catastrophic illnesses, pregnant women and people with disabilities. In this regard, special treatment was given as to what relates to public health, but also because of the inclusion productive and labor sector through reforms to the Labour Code, Organic Law of Public Service and the Law organic Disabilities. Regarding access to jobs for people with disabilities, he revolutionized the Law for the disabled, as is all access to jobs, equal and coupled to each type of disability, up to a maximum of 4% of workers or servers within each institution. In other words: For every twenty workers or servants in public institutions or private companies, the employer is required to include in their payroll a disabled person. The population rate of people with disabilities evolves over time. Based momentum inclusive education policy formulated by the state, also it has been increasing the professional rate, the same as saving the adversity of their physical limitations, acquire their title third or fourth level in national and international universities recognized in our country , joining the productive sector of our country. I allowed myself to investigate the statistics of persons with disabilities who records the CONADIS until August of the year two thousand and fifteen, as well as the percentage of people including the labor sector, data from the Ministry of Labor and Human Resources; this in order to establish the effective implementation of the law in this area, according to population growth of this vulnerable sector. Concomitantly the legal framework that should hold us in this research work, regarding the terms "capacity" and "disability" of human beings, philosophically and as a sentence of psychological motivation say: Disability is the size of the human mind so that with the way they acquire their thoughts, will build its development and achieve its objectives. For these reasons, and mother of two disabled people who are close to graduating from lawyers with me, I have considered of social interest and importance the proposed topic, in order to contribute to the welfare of this sensitive population of our society, proposing the percentage increase of 4% to 8% of people with disabilities to be included on the payroll of employees in the public sector and the private sector.